Structural characterization of polysaccharides recovered from extraction residue of ginseng root saponins and its fruit nutrition preservation performance - Sun, Jing; Zhong, Xinyu; Sun, Dandan; Cao, Xinxin; Yao, Fan; Shi, Lingling; Liu, Yujun (Frontiers in Nutrition, 2022)
Polysaccharides recovered from extraction residue of ginseng root saponins, i.e., ginsenosides-extracting residue polysaccharides (GRP), were separated into two fractions, GRP-1 and GRP-2. Fourier infrared and nuclear magnetic resonance spectra, as well as high-performance liquid chromatography and gel permeation chromatography measurements, showed GRP-1 was composed of mainly starch-like glucans and GRP-2, relatively a smaller portion, was a mixture of heteropolysaccharides composed of starch-like glucans, rhammogalacturonan-Ⅰ pectin, and arabinogalactans, and they had similar molecular weights. These results proved that the structure of GRP was not destroyed and GRP still maintained strong antioxidant activities. In addition, GRP coating on surfaces of fruit slowed their deterioration and maintained their nutritional effects. Correlation and PCA analyses on various quality and antioxidant parameters supported the above findings and a possible mechanism in fruit preservation was then proposed. Knowing the structural features and bioactivities of GRP gives insights into its application. Specifically, GRP serves as an environmentally friendly coating can be used to preserve the nutrients and other quality indicators of strawberries and fresh-cut apples, paving the way for future new approaches for food preservation using polysaccharides or other natural products.